“Descubiertas” las hembras ovíparas de Xerobion georgii (Mier Durante & Nieto Nafría, 1991) (Hemiptera, Aphididae, Aphidinae, Aphidini) - N. Pérez Hidalgo; M. P. Mier Durante; J. M. Nieto Nafría (Graellsia, 2007)
No disponible